2016
DOI: 10.1182/blood-2015-10-677633
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vitamin K–dependent carboxylase mutations that cause bleeding and nonbleeding disorders

Abstract: Key Points• CRISPR-Cas9-mediated GGCX knockout cell-based assay clarifies the correlation between GGCX genotypes and their clinical phenotypes.• A GGCX mutation decreases clotting factor carboxylation and abolishes MGP carboxylation, causing 2 distinct clinical phenotypes.Vitamin K-dependent coagulation factors deficiency is a bleeding disorder mainly associated with mutations in g-glutamyl carboxylase (GGCX) that often has fatal outcomes. Some patients with nonbleeding syndromes linked to GGCX mutations, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…The cDNA of GGCX or its mutants was cloned into mammalian expression vector pBudCE4.1-Met.Luc and transiently expressed in the GGCX-deficient dual-reporter cells as described in Section 3.3. Four hours posttransfection, the transfection medium was replaced by complete growth medium containing 11 μ M vitamin K and incubated for 48 h. Carboxylation activity was determined by measuring the level of carboxylated reporter proteins in the cell culture medium using sandwich-based ELISA (Tie et al, 2016). …”
Section: Functional Study Of Ggcx Using Crispr-cas9-mediated Gene mentioning
confidence: 99%
See 2 more Smart Citations
“…The cDNA of GGCX or its mutants was cloned into mammalian expression vector pBudCE4.1-Met.Luc and transiently expressed in the GGCX-deficient dual-reporter cells as described in Section 3.3. Four hours posttransfection, the transfection medium was replaced by complete growth medium containing 11 μ M vitamin K and incubated for 48 h. Carboxylation activity was determined by measuring the level of carboxylated reporter proteins in the cell culture medium using sandwich-based ELISA (Tie et al, 2016). …”
Section: Functional Study Of Ggcx Using Crispr-cas9-mediated Gene mentioning
confidence: 99%
“…Using this cell-based assay, we first studied GGCX mutations found in a child with severe cerebral bleeding and comorbid Keutel syndrome, a nonbleeding malady caused by functional defects of MGP (Tie et al, 2016). Clinical data showed that high doses of vitamin K administration improved the bleeding diathesis of the patient, but not the functional defect of MGP.…”
Section: Functional Study Of Ggcx Using Crispr-cas9-mediated Gene mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that this splice-site mutation could result in several variant mRNA transcripts of GGCX, as has previously described for other genes (Gallinaro et al , 2006; Kallabi et al , 2015). The affected patients reported by Kariminejad et al (2014) have normal coagulation factor carboxylation, but defects in their MGP carboxylation; it is therefore possible that some of the mRNA transcript may produce a GGCX mutant protein that causes MGP-carboxylation defects but has a smaller effect on coagulation factor carboxylation, as we have previously observed in a VKCFD patient (Tie et al , 2016). …”
Section: To the Editormentioning
confidence: 73%
“…This approach, unlike the traditional in vitro GGCX activity assay, allows us to assess the functionality of GGCX using its natural protein substrates in a cellular milieu that requires the enzyme to interact with its physiologic components for VKD carboxylation (Tie et al , 2016). Our result shows that the GGCX-Δex3 mutant abolished carboxylation activity for both reporter proteins (Figure 1a).…”
Section: To the Editormentioning
confidence: 99%